TRABALHO E CÁRCERE | Work and prison (Trabalho & Educação, 2017)
The penalty of prison had as its essence forced labor. This was considered a complement to the penalty. With the development of the penitentiary science, the work has been demanded of the inmate since it was done in dignified conditions and in a way that did not represent an aggravation of the sentence. The current trend is equalizing the work of arrested prisoners with that one executed out of walls. The LEP conceptualizes prison work as a social duty and condition of human dignity. Its purpose should be educational and productive, so, useful and making maximum approach to free work. The doctrine also classifies work as a right of the detainee. The execution of the work by the condemned person entails nominal reduction of time in prison. If the work is not carried out it will have consequences, depending on the type. The foundations of prisons work stimulate important reflections on the execution of the custodial sentence and functions.___A pena privativa de liberdade tinha como sua essência o trabalho forçado. Este era considerado um complemento da pena. Com o desenvolvimento do penitenciarismo, o trabalho passou a ser exigido do condenado desde que fosse feito em condições dignas e de modo que não representasse um agravamento da pena. A tendência atual é a equiparação do trabalho do preso àquele executado em meio aberto. A Lei de Execução Penal (LEP) conceitua o trabalho prisional como dever social e condição de dignidade humana. Sua finalidade deve ser educativa e produtiva, logo, útil e com máxima aproximação ao trabalho livre. A doutrina também classifica o trabalho como um direito do detento. A realização do trabalho pela pessoa presa acarreta redução nominal de pena e a não realização terá consequências, a depender do tipo de trabalho que deveria ser executado. Os fundamentos do trabalho nas prisões estimulam importantes reflexões sobre a execução da pena privativa de liberdade e suas funções.